(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article presents a linguocognitive analysis of time concepts as reflected in English and Russian proverbs. Drawing on cognitive linguistics, the study examines how different cultures conceptualize time similarly through metaphorical and proverbial expressions, highlighting both shared and divergent perceptions. Proverbs are categorized according to their representation of time as value – as a resource for everything, as a teacher – providing with knowledge and wisdom, as healer – as a curative force, as a judge – an impartial evaluator, as a cycle – part of the natural order and as opportunity – time as a chance. The analysis reveals that both English and Russian proverbs emphasize the value of timely action, yet cultural nuances shape their expressions and underlying attitudes toward time. English proverbs often employ vivid imagery and imperatives to stress seizing the moment, while Russian proverbs combine practical wisdom with moral and ethical reflections.